2017
DOI: 10.1002/ajh.24908
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive score for delayed hemolytic transfusion reaction in adult patients with sickle cell disease

Abstract: Delayed hemolytic transfusion reaction (DHTR) is a life-threatening complication of transfusion in sickle cell disease (SCD). The frequency of DHTR is underestimated because its symptoms mimic those of vaso-occlusive crisis and antibodies (Abs) are often not detectable. No predictive factors for identifying patients likely to develop DHTR have yet been defined. We conducted a prospective single-center observational study over 30 months in adult sickle cell patients. We included 694 transfusion episodes (TEs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
117
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 40 publications
4
117
2
4
Order By: Relevance
“…Previous reports have shown that complement activation most likely from the alternative pathway may be involved in the pathogenesis of DHTRs with hyperhemolysis in SCD patients with no identifiable alloantibody . However, it should be noted that some patients who experience DHTRs experience full recovery to baseline Hb levels without any specific immunosuppressive intervention …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports have shown that complement activation most likely from the alternative pathway may be involved in the pathogenesis of DHTRs with hyperhemolysis in SCD patients with no identifiable alloantibody . However, it should be noted that some patients who experience DHTRs experience full recovery to baseline Hb levels without any specific immunosuppressive intervention …”
Section: Discussionmentioning
confidence: 97%
“…These recommendations, however, would need to be tested prospectively to definitively demonstrate their efficacy at preventing or treating DHTRs. Given the appreciable rate of DHTRs coupled with the potentially devastating consequences that can ensue, additional mechanistic studies are critically needed to determine optimal treatment options for this vulnerable patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong need for additional educational resources for patients and caregivers with SCD receiving transfusion therapy, with focus on transfusion benefits, adverse reactions, and the importance of keeping a personal record of transfusion episodes and reactions. This education is of particular importance to those receiving episodic transfusion therapy as well as CTT, as delayed hemolytic transfusion reactions occur more frequently in episodically transfused patients with SCD and may be under‐recognized or misdiagnosed …”
Section: Discussionmentioning
confidence: 99%
“…Patients with sickle cell disease (SCD) often receive unnecessary red blood cell (RBC) transfusions leading to complications which include alloimmunization, hyperhemolysis, and iron overload [1-3]. An under-recognized risk of iatrogenic iron overload in patients with SCD is an increased susceptibility to infections with siderophilic, or “iron-loving,” bacteria.…”
mentioning
confidence: 99%